Working in a Problem-based Manner with Mathematics and Crafts Gives Meaning to Mathematics at Danish Vocational Schools - Dahl, Bettina; Hansen, Søren; Schaarup, Jette; Lindenskov, Lena; Justesen, Frank (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Students at Danish vocational schools often struggle with learning mathematics and finding it relevant. In response to this, the project KLUMP (“competence lifting of mathematics teachers at vocational schools”) offered professional development of mathematics teachers and craft teachers through facilitating collaboration on creating teaching materials bridging mathematics and the craft. Five teams were established consisting of one mathematics and one craft teacher in the following areas: carpenter, blacksmith, mason, mechanics, and electrician. The teachers joined KLUMP voluntarily, and the school management supported KLUMP by coordinating time schedules and joining project seminars. The teachers selected relevant topics, where they developed, tested, evaluated, and refined their teaching material. The teachers received inspiration in workshops on, e.g. emergent modelling, inquiry- and problem-based learning, and concepts such as self-efficacy. A central theme is Jaworski’s notion about learning communities. KLUMP found that the frameworks of a “bridge” between mathematics and crafts and emergent modelling were easy for the teachers to use. The students were happy when they experienced the bridge. Structures such as timetable planning, teacher allocation, and institutional support were essential for KLUMP to become successful.